Heat stress responses vary during floret development in European spring barley cultivars - Callens, Cindy; Fernandez-Goméz, José; Tucker, Matthew R.; Zhang, Dabing; Wilson, Zoe A. (Frontiers in Plant Science, 2023)
The Poaceae, or grasses, include many agriculturally important cereal crops such as rice (Oryza sativa), maize (Zea mays), barley (Hordeum vulgare) and bread wheat (Triticum aestivum). Barley is a widely grown cereal crop used for stock feed, malting and brewing. Abiotic stresses, particularly global warming, are the major causes of crop yield losses by affecting fertility and seed set. However, effects of heat stress on reproductive structures and fertility in barley have not been extensively investigated. In this study we examined three commercial European spring barley varieties under high temperature conditions to investigate the effects on floret development. Using a combination of fertility assays, X-ray micro computed tomography, 3-dimensional modelling, cytology and immunolabelling, we observed that male reproductive organs are severely impacted by increased temperature, while the female reproductive organs are less susceptible. Importantly, the timing of stress relative to reproductive development had a significant impact on fertility in a cultivar-dependent manner, this was most significant at pollen mitosis stage with fertility ranged from 31.6-56.0% depending on cultivar. This work provides insight into how heat stress, when applied during male pollen mother cell meiosis and pollen mitosis, affects barley fertility and seed set, and also describes complementary invasive and non-invasive techniques to investigate floret development. This information will be used to identify and study barley cultivars that are less susceptible to heat stress at specific stages of floral development.